2005
DOI: 10.1083/jcb.200412024
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress signaling transmitted by ATF6 mediates apoptosis during muscle development

Abstract: Although apoptosis occurs during myogenesis, its mechanism of initiation remains unknown. In a culture model, we demonstrate activation of caspase-12, the initiator of the endoplasmic reticulum (ER) stress-specific caspase cascade, during apoptosis associated with myoblast differentiation. Induction of ER stress-responsive proteins (BiP and CHOP) was also observed in both apoptotic and differentiating cells. ATF6, but not other ER stress sensors, was specifically activated during apoptosis in myoblasts, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
209
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(231 citation statements)
references
References 23 publications
18
209
2
2
Order By: Relevance
“…130,131 The functional importance of JNK activation in the ER stress pathway has not been fully explored, but ASK1 À/À cells are partially resistant to ER stress-induced apoptosis, 132 suggesting that JNK may promote apoptosis in this context. A recent report also indicates that ATF6 might mediate a proapoptotic signal during normal myoblast development, 133 implicating this upstream UPR sentinel in apoptotic pathways as well.…”
Section: Esr and Apoptosismentioning
confidence: 96%
“…130,131 The functional importance of JNK activation in the ER stress pathway has not been fully explored, but ASK1 À/À cells are partially resistant to ER stress-induced apoptosis, 132 suggesting that JNK may promote apoptosis in this context. A recent report also indicates that ATF6 might mediate a proapoptotic signal during normal myoblast development, 133 implicating this upstream UPR sentinel in apoptotic pathways as well.…”
Section: Esr and Apoptosismentioning
confidence: 96%
“…11,12,24,25 During myogenesis in vitro, as many as 50% of myoblasts reportedly undergo apoptosis, 9,10,15 although the extent of cell death likely depends on origin of the myoblasts and the culture conditions used for each study. Myoblasts may undergo apoptosis during myogenesis as a means of regulating muscle size.…”
Section: Discussionmentioning
confidence: 99%
“…14 Caspase-12 is also activated during muscle differentiation, and has been implicated in the initiation of apoptosis that occurs during myogenesis. 15 Activated caspases are inhibited by the IAP family of proteins, thus the IAPs serve as a shield to the final execution of apoptosis. 17 Expression levels of IAPs are dynamic, and can be regulated at the transcriptional, post-transcriptional, and post-translational levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] ER stress activates IRE1 that splices the Xbp1 mRNA generating an isoform encoding the XBP1 transcription factor. 21,22 Quantification of the mRNA-seq reads that cover the splice junctions in exon 4 of the Xbp1 mRNA in the ShSC, ShA and ShB cells showed that around half the Xbp1 mRNA was spliced in the ShSC cells, but not in TEAD4 knockdown cells (Supplementary Figure 5A).…”
mentioning
confidence: 99%